Does Helicobacter pylori infection influence the major postoperative complication rate after sleeve gastrectomy? A retrospective cohort study in an endemic region - Kürşat Rahmi Serin,; Ümit Akyüz,; Burçin Batman,; Derya Salim Uymaz,; Hasan Altun, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Helicobacter pylori infection is very common in Eastern countries. Little is known about the impact this infection has on bariatric surgery outcomes. This retrospective cohort study conducted on obese Turkish adults who underwent sleeve gastrectomy at a single center aimed to determine the prevalence of H. pylori infection and the effect of this infection on the rate of early major postoperative complications. Materials and Methods: All consecutive patients who underwent sleeve gastrectomy for obesity between 2014 and 2015 and who had complete data were enrolled. A single surgeon performed all procedures. All resected specimens were sent to pathology for analysis. Results: Of the 460 patients who met the eligibility criteria, 326 (71%) were female. The average (±standard deviation) age and body mass index were 37.5±10.0 years and 42.7±7.7 kg/m2, respectively. Histology revealed that 150 (33%) patients had H. pylori infection. The H. pylori-infected group developed two complications (leakage and intra-abdominal collection). The uninfected group developed three complications (all bleeding related). The two groups did not differ significantly regarding postoperative complication rates (1.3% vs. 1.0%; p=0.717). Conclusion: H. pylori infection did not affect the rate of early complications after sleeve gastrectomy. This suggests that H. pylori screening or eradication policy is not essential for asymptomatic candidates who have undergone sleeve gastrectomy. Cite this article as: Serin KR, Akyüz Ü, Batman B, Salim Uymaz D, Altun D.  Does Helicobacter pylori infection influence the major postoperative complication rate after sleeve gastrectomy? A retrospective cohort study in an endemic region. Turk J Gastroenterol 2018; 29: 379-83.